The IEBM handbook of economics - Lazonick, William (London : Thomson, 2002)
The book offers a comprehensive and authoritative analysis on the major economic issues of our day. it provides an important reference work and learning tool for students of business and management, economists among them.
Includes bibliographical references and index.
uaj 18/09/2014
Reference
Keywords: Economics -- Handbooks, manuals, etc